2012
DOI: 10.1097/qad.0b013e32834ff690
|View full text |Cite
|
Sign up to set email alerts
|

The association between Mycoplasma genitalium and HIV-1 acquisition in African women

Abstract: This is the first longitudinal study to assess the relationship between M. genitalium and HIV-1 acquisition. If findings from this research are confirmed, M. genitalium screening and treatment among women at high risk for HIV-1 infection may be warranted as part of an HIV-1 prevention strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 30 publications
2
32
0
Order By: Relevance
“…Importantly, cervicitis has been associated with increased HIV shedding, and treatment of the condition reduces both viral shedding and the presence of virus-infected cells in cervical secretions (51)(52)(53). Having been shown to enhance susceptibility to HIV infection (54,55), and with cross-sectional associations with HIV infection in more than 20 studies (56), continued investigation of M. genitalium remains important, as antibiotic-resistant strains continue to emerge worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, cervicitis has been associated with increased HIV shedding, and treatment of the condition reduces both viral shedding and the presence of virus-infected cells in cervical secretions (51)(52)(53). Having been shown to enhance susceptibility to HIV infection (54,55), and with cross-sectional associations with HIV infection in more than 20 studies (56), continued investigation of M. genitalium remains important, as antibiotic-resistant strains continue to emerge worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has implicated the bacterium in clinically significant disease in females (2,3). Additional studies suggest that M. genitalium infection promotes HIV acquisition (4)(5)(6) and virus shedding (7,8). Moreover, in a recent meta-analysis, Lis et al (9) reported significant associations between M. genitalium infection and cervicitis, pelvic inflammatory disease, preterm birth, and spontaneous abortion.…”
mentioning
confidence: 99%
“…In women, it has been associated with cervicitis, pelvic inflammatory disease, and infertility (1,(3)(4)(5)(6)(7) and studies have also suggested that it plays an important role in HIV acquisition and transmission (8,9). The exact rates of M. genitalium prevalence have been reported in a limited number of studies, with prevalences of 0.8% to 2.3% among young women and 1.1% to 6.9% among young men (10)(11)(12)(13)(14).…”
mentioning
confidence: 99%